2021
DOI: 10.1158/2159-8290.cd-21-0190
|View full text |Cite
|
Sign up to set email alerts
|

WNT as a Driver and Dependency in Cancer

Abstract: The WNT signaling pathway is a critical regulator of development and adult tissue homeostasis and becomes dysregulated in many cancer types. Although hyperactivation of WNT signaling is common, the type and frequency of genetic WNT pathway alterations can vary dramatically between different cancers, highlighting possible cancer-specific mechanisms for WNT-driven disease. In this review, we discuss how WNT pathway disruption contributes to tumorigenesis in different organs and how WNT affects the tumor cell and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
103
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(104 citation statements)
references
References 202 publications
1
103
0
Order By: Relevance
“…These pathways included adherens junction, TGF-beta pathway, Wnt pathway, Hippo pathway, mTOR pathway etc. (Ediriweera et al, 2019;Li et al, 2021;Parsons et al, 2021;Sabbadini et al, 2021). PPI network showed that three hub proteins, SOX9, YAP1 and GSK3β, were located in the key positions, and all of them were involved in Wnt and Hippo signaling pathways (Stewart, 2014;Ediriweera et al, 2019;Li et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…These pathways included adherens junction, TGF-beta pathway, Wnt pathway, Hippo pathway, mTOR pathway etc. (Ediriweera et al, 2019;Li et al, 2021;Parsons et al, 2021;Sabbadini et al, 2021). PPI network showed that three hub proteins, SOX9, YAP1 and GSK3β, were located in the key positions, and all of them were involved in Wnt and Hippo signaling pathways (Stewart, 2014;Ediriweera et al, 2019;Li et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…We then performed in vitro and in vivo assays, which validated that overexpression of IRF-2 in GC cell lines resulted in both the capability of colony formation and cell proliferation as well as the upregulation of AMER-1 protein levels and activation of the Wnt/β-catenin signaling pathway; IRF-2 knockdown resulted in the opposite trend. The Wnt signaling pathway has been recognized as a promoter in many types of cancer, and its activity is controlled by a series of tumor suppressors [ 25 , 26 ]. Ghafar suggested that the Wnt cascade is activated by MTDH, and exerts oncogenic functions in colorectal cancer [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Any disturbance (e.g., mutations or activation) in this molecular pathway leads to pathological situations [57] . Recently, Deng et al [58] studied the involvement of Indian -Expression of stemness markers (CD133, CXCR4, Nanog, Otc4) -K7M2 mouse cell line [28] -In vivo properties of tumor-initiating cells -318-1, P932, and K7M2 mouse cell lines and KHOS and MNNG/HOS human cell lines [29] -U2OS human cell line [30] CD117, Stro-1 -Drug resistance (ABCG2): resistance to methotrexate, cisplatin -MG63, MNN/HOS, and 143B human cell lines and patient-derived cells [31] -Sphere formation -Expression of stemness markers (Sox2, Oct3/4, Nanog) -SaOS2, MG63, and U2OS human cell lines [32] -Expression of ABCG2 and MDR1 -Primary cultures of human cancer cells and MG63 human cell line [33] -Expression of ABCB1, ABCC2, and the metastasisassociated genes β4-integrin, ezrin, MMP-13, and CXCR4…”
Section: Molecular Regulation Of Cancer Stem-like Cells In Osteosarcomamentioning
confidence: 99%
“…They demonstrated that deleting Ptch1 in mice was associated with an increase in Wnt member expression and the development of skeletal diseases, including osteosarcoma. Interestingly, inhibiting the Wnt/β-catenin pathway abolished the development of osteosarcoma, highlighting the key role played by this molecular pathway in the pathogenesis of bone sarcomas [58] . The Wnt/β-catenin pathway might be the link among tumor development, drug resistance, and CSCs in osteosarcoma.…”
Section: Molecular Regulation Of Cancer Stem-like Cells In Osteosarcomamentioning
confidence: 99%